Comparison of Time Trends of Cardiovascular Disease Risk Factors and Framingham Risk Score Between Patients With and Without Acute Coronary Syndrome Undergoing Percutaneous Intervention Over the Last 17 Years: From the Mayo Clinic Percutaneous Coronary Intervention Registry - Lee, Moo‐Sik (Clin Cardiol, 2015)
BACKGROUND: The objective of this study was to investigate cardiovascular disease risk factor (cvRF) profiles and compare their trends over 17 years in patients with and without acute coronary syndrome (ACS) undergoing percutaneous coronary intervention (PCI). HYPOTHESIS: Time trends of cvRF are different between ACS and non‐ACS patients. METHODS: This study was a time‐trend analysis from 1994 to 2010 within the Mayo Clinic PCI registry. Outcome measures were incidence and prevalence of cvRF, including the Framingham Risk Score (FRS), at the time of admission for PCI. RESULTS: Age of non‐ACS patients was higher than that of ACS patients, and age distribution slightly shifted toward older age in both groups (P for trend <0.001). There was no difference in FRS between the 2 groups; however, 10‐year cardiovascular disease risk (%) remained higher in non‐ACS than in ACS patients, decreasing over time. Diastolic blood pressure and high‐density lipoprotein cholesterol were higher in non‐ACS patients, but total cholesterol and low‐density lipoprotein cholesterol were higher in ACS patients, with an improving trend over time. Prevalence of diabetes mellitus, hypertension, and history of hypercholesterolemia were higher in non‐ACS patients, increasing over time. Smoking did not change over time. Use of most medications increased over time in both groups. CONCLUSIONS: Most cvRFs and their time trends exhibited statistically significant differences between ACS and non‐ACS patients, except systolic blood pressure, body mass index, and history of myocardial infarction. A new risk‐factor profile assessment may be needed for stratification of PCI patients according to ACS and non‐ACS status. Clinical and public‐health interventions should consider different approaches to ACS and non‐ACS patients.